2001
DOI: 10.1111/j.1365-2486.2001.00437.x
|View full text |Cite
|
Sign up to set email alerts
|

CO2 exchange in an organic field growing barley or grass in eastern Finland

Abstract: The CO 2 dynamics were measured in an organic soil in eastern Finland during the growing season and wintertime, and the annual CO 2 balance was calculated for plots where barley or grass was grown. During the summer, the CO 2 dynamics were measured by transparent and opaque chambers using a portable infrared gas analyser for the CO 2 analyses. During the winter, the CO 2 release was measured by opaque chambers analysing the samples in the laboratory with a gas chromatograph. Statistical response functions for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
51
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 29 publications
11
51
1
Order By: Relevance
“…Findings supporting our results, with a higher emission rate at intermediate groundwater levels compared with low (dry soil), have been reported by Davidson et al (1998), Chimner and Cooper (2003) and Kechavarzi, C. et al (2007). Nieveen et al (2005) found that the distance to the groundwater did not influence the emission of CO 2 and Aerts and Ludwig (1997) and Maljanen et al (2001) reported similar results. Laiho (2006) emphasises the complexity of peatland behaviour following persistent lowering of the groundwater level, with multiple interactions between many factors such as time scale and soil type.…”
Section: Effect Of Water Table Regulation On Emission Ratessupporting
confidence: 82%
See 1 more Smart Citation
“…Findings supporting our results, with a higher emission rate at intermediate groundwater levels compared with low (dry soil), have been reported by Davidson et al (1998), Chimner and Cooper (2003) and Kechavarzi, C. et al (2007). Nieveen et al (2005) found that the distance to the groundwater did not influence the emission of CO 2 and Aerts and Ludwig (1997) and Maljanen et al (2001) reported similar results. Laiho (2006) emphasises the complexity of peatland behaviour following persistent lowering of the groundwater level, with multiple interactions between many factors such as time scale and soil type.…”
Section: Effect Of Water Table Regulation On Emission Ratessupporting
confidence: 82%
“…The influence of water table level was questioned by Joosten & Clarke (2002), who found that the highest mineralisation rate was observed with the groundwater level at 80-90 cm depth, but that a groundwater level at 17-60 cm still had 80% of the maximum mineralisation rate. Several authors (Freeman et al, 1996;Aerts and Ludwig, 1997;Maljanen et al, 2001;Campbell et al, 2004;Lafleur et al, 2005;Nieveen et al, 2005) argue that the correlation between groundwater depth (and therefore top soil moisture content) and CO 2 emission is poor. N 2 O emissions from cultivated peat soils show a great variation in time and space and depend on a number of factors (Regina et al, 2004) such as drainage, peat type, climate and fertilisation.…”
Section: Introductionmentioning
confidence: 99%
“…The statistical analysis showed that CO 2 emissions from the Örke soil were significantly higher than those from the Majnegården soil during the whole year for both watertable levels, with an average daytime emission rate of 483 ± 6.9 mg CO 2 m -2 h -1 from Örke soil and 360 ± 7.5 mg CO 2 m -2 h -1 from Majnegården soil. These CO 2 emission results were in the same range as those reported by Maljanen et al (2001) but somewhat higher compared with other investigations. Joosten and Clarke (2002) and Wessolek et al (2002) found that drained grassland emitted about 170-200 mg CO 2 m -2 h -1 , while Kasimir- Klemedtsson et al (1997) reported that CO 2 flux from Majnegården measured in the field, including root respiration of 38%, was 276 mg CO 2 m -2 h -1 .…”
Section: Co 2 Emissionssupporting
confidence: 79%
“…Vourlites et al, 1993;Oechel et al, 1993Oechel et al, , 1998Oechel et al, , 2000Jensen et al, 1996;Alm et al, 1997Alm et al, , 2007Goulden and Crill, 1997;Christensen et al, 1998;Tuittila et al, 1999;Maljanen et al, 2001;Xu and Qi, 2001;Bubier et al, 2002;Nykänen et al, 2003;Pumpanen et al, 2003;Burrows et al, 2004;Heijmans et al, 2004;Drösler, 2005;Reth et al, 2005;Laine et al, 2006;Wang et al, 2006). Usually, the authors justify the use of linear regression by keeping the closure time short and assuming the concentration change over time to be still in the linear range.…”
mentioning
confidence: 99%
“…Jensen et al, 1996;Xu and Qi, 2001;Pumpanen et al, 2003Pumpanen et al, , 2004Reth et al, 2005;Wang et al, 2006). Also, it is often applied to quantify the net CO 2 exchange between the atmosphere and low-stature canopies typical for tundra (Vourlites et al, 1993;Christensen et al, 1998;Oechel et al, , 1998Oechel et al, , 2000Zamolodchikov and Karelin, 2001), peatlands (Alm et al, , 2007Tuittila et al, 1999;Bubier et al, 2002;Nykänen et al, 2003;Burrows et al, 2004;Drösler, 2005;Laine et al, 2006), forest understorey vegetation (Goulden and Crill, 1997;Heijmans et al, 2004) and agricultural crop stands (Dugas et al, 1997;Wagner et al, 1997;Maljanen et al, 2001;Steduto et al, 2002). Advantageously, the closed-chamber method is relatively low in cost and power consumption, simple to operate and can therefore be used in remote, logistically difficult areas.…”
mentioning
confidence: 99%